PENGARUH PERAWATAN METODE KANGGURU TERHADAP PRODUKSI ASI PADA IBU DAN KEPERCAYAAN DIRI IBU PRIMIPARA DALAM MERAWAT BAYI DI WILAYAH KERJA PUSKESMAS BATU AJI KOTA BATAM TAHUN 2018 - Hutabarat, Yeslina; Aryaneta, Yenni (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2019)
Kangaroo Mother Care (KMC) is a treatment for birth weight infants. Kangaroo Method Treatment (KMT) can increase the bond of love between a mother and her baby, facilitate the baby in fulfilling nutritional needs, prevent infection and shorten the period of hospitalization so as to reduce treatment costs. The purpose of this study was to find out the effect of kangaroo method treatment on maternal breast milk production and primiparous mothers’ self-confidence in caring for babies at Puskesmas Batu Aji, Batam in 2018 with a population of 60 primiparous mothers. Data analysis applied T-Test analysis technique. The results of the research showed that the average  maternal milk production was not given PMK 1.40 ± 0.498 and that given PMK 2.63 ± 0.49, while the confidence / ability to care for babies in mothers who were not given PMK 13.63 ± 2.38 and given PMK 30.93 ± 3.02. The conclusion of this study is the Effect of Kangaroo Method Treatment (KMT) on Maternal Breastmilk Production and Self-Confidence in primiparous mothers caring for babies at Puskesmas Batu Aji work area. It is suggested for mothers to be more actively seeking information about KMT so that respondents can do baby care in a more efficient way.